Multi-objective Optimization Design of RV Reducer Considering the Cycloid Gear Profile Modification - Wang Quan; Zeng Lilei; Qin Zhengzheng (Jixie chuandong)
In view of the fact that the influence of cycloid gear profile modification on contact force is not taken into account in the structural design of RV reducer，a multi-objective optimization design method for the structure of RV reducer considering cycloid gear profile modification is proposed.Combining the theory of tooth profile modification with the calculation of contact stress of cycloidal gear，considering the factors of volume，efficiency and contact stress，an optimization mathematical model with small volume，high efficiency and low contact stress of cycloidal gear as multi-objective function is established.The solution is carried out by using NSGA-II algorithm，and compared with single-objective optimization method.The results show that compared with the original design，the volume of RV reducer decreases by 21.24%，the efficiency increases by 2.03%，and the contact stress of cycloid wheel decreases by 20.26%.Meanwhile，the multi-objective optimization method has higher comprehensive performance than the single-objective optimization method.